2022
DOI: 10.3390/nu14194116
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Polysaccharides as Modulators of the Gut Microbiota Ecosystem: An Update on Their Impact on Health

Abstract: A polysaccharide is a macromolecule composed of more than ten monosaccharides with a wide distribution and high structural diversity and complexity in nature. Certain polysaccharides are immunomodulators and play key roles in the regulation of immune responses during the progression of some diseases. In addition to stimulating the growth of certain intestinal bacteria, polysaccharides may also promote health benefits by modulating the gut microbiota. In the last years, studies about the triad gut microbiota–po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 139 publications
0
17
0
Order By: Relevance
“…Polysaccharides have been proved to contribute significantly to the metabolic abilities of gut microbiota, such as the production of SCFAs. Polysaccharides and the production of SCFAs by the gut microbiota have been reported to improve mucus secretion and increase tight-junction protein expression [ 72 , 73 ]. Metabolites produced by gut microbiota have also been shown to improve cognitive function through modulation of the brain–gut axis [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…Polysaccharides have been proved to contribute significantly to the metabolic abilities of gut microbiota, such as the production of SCFAs. Polysaccharides and the production of SCFAs by the gut microbiota have been reported to improve mucus secretion and increase tight-junction protein expression [ 72 , 73 ]. Metabolites produced by gut microbiota have also been shown to improve cognitive function through modulation of the brain–gut axis [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, we found that the number of subjects in the uric acid parameter changed significantly comparing pre-intervention and post-intervention. These results may be associated with the modulation exerted by inulin on the gut microbiome, which is capable of modulating uric acid levels [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This special issue includes eight papers, seven of them are original publications [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ], and one review [ 12 ]. Overall, these works highlight mechanisms involving changes in microbiota affected by polysaccharides as well as the evaluation of dietary polysaccharides–health links.…”
mentioning
confidence: 99%
“…Finally, the review included in this collection presents a summary of recent knowledge regarding how dietary polysaccharides affect gut microbiota composition and host health. The immunomodulatory properties of certain polysaccharides are crucial to the regulation of immune responses during the progression of certain diseases [ 12 ]. It is believed that polysaccharides may also have health benefits by modulating the gut microbiota, besides stimulating the growth of certain intestinal bacteria.…”
mentioning
confidence: 99%
See 1 more Smart Citation